2019
DOI: 10.1001/jamaneurol.2018.4147
|View full text |Cite|
|
Sign up to set email alerts
|

Risk of Depression and Anxiety in Adults With Cerebral Palsy

Abstract: This cohort study assesses depression and anxiety in adults with cerebral palsy compared with age-, sex-, and practice-matched adults with cerebral palsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(126 citation statements)
references
References 49 publications
4
111
1
4
Order By: Relevance
“…In the current study, we found that adults with CP had higher adjusted odds of pain, osteoarthritis, depressive disorders, and anxiety disorders, which is consistent with previous studies. 5,9,10 Pediatric chronic pain is associated with increased risk for lifetime depressive and anxiety disorders. 41 Further, osteoarthritis may exacerbate pain, which can negatively affect function and activities of daily living, 42 thus posing another mechanism for adverse mental health processes and low social participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, we found that adults with CP had higher adjusted odds of pain, osteoarthritis, depressive disorders, and anxiety disorders, which is consistent with previous studies. 5,9,10 Pediatric chronic pain is associated with increased risk for lifetime depressive and anxiety disorders. 41 Further, osteoarthritis may exacerbate pain, which can negatively affect function and activities of daily living, 42 thus posing another mechanism for adverse mental health processes and low social participation.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10] Consequently, adults with CP are at risk of early development of several medical conditions that incur excess health care costs and represent a considerable patient and caregiver burden, including chronic pain, 11 heightened fracture susceptibility, 8 and non-communicable diseases (eg, cardiometabolic, mental health). 9,10,12,13 There is very little knowledge about the life-course health development and healthy aging process among adults with CP, resulting in insufficient clinical care for these populations. At present, the US health care system is not well-designed to meet the greater demands imposed by individuals with neurological conditions, 14,15 thus further increasing risk of health disparities that may otherwise be prevented or lessened.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that the prevalence of obesity-related noncommunicable diseases and mortality are higher for adults with CP than the general population. 22,28,30 Since many chronic disease processes initiate in childhood, this systematic scoping review highlights the need for further clinical and translational research regarding body fat assessment and biology, because of its potential impact on growth, function and health among children and young people with CP.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to note that OA is implicated in the pathogenesis of cardiometabolic diseases (37) and mental health disorders (38) among adults without CP. Adults with CP have elevated cardiometabolic disease prevalence (9), higher incidence of depression and anxiety (39), and 2-3-fold increased risk of cardiovascular mortality (40) compared with adults without CP. While it is unknown how OA associates with non-communicable diseases and mortality among adults with CP, OA has been shown to amplify daily pain levels and negatively affect function and activities of daily living for adults without CP (1).…”
Section: Discussionmentioning
confidence: 99%